Analysis of Halal Tourism Implementation From The Maqashid Syariah Perspective In Selayar District - Bado, Basri; Zulkifli, Zulkifli; Susono, Juhasdi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
The Islamic economy is now an important part of the global economy, with one of its sectors, namely halal tourism, experiencing significant growth. The presence of maqashid sharia can strengthen the meaning of halal in tourism activities. Therefore, this research aims to determine the form of implementation of maqashid sharia values, which consist of protecting religion, protecting reason, and protecting property, as well as its influence on tourist utility. The data in this study is primary data obtained through a questionnaire with a Likert scale of 1-3, with a population of Muslim tourists aged 21 years and over who have visited one of the 10 halal tourist destinations in Selayar Regency. The analytical method used is Multiple Linear Regression Analysis. The research results show that the maqashid sharia values ​​(protecting religion, protecting reason, and protecting property) have been implemented in halal tourist destinations in Selayar Regency and can significantly influence tourist utility.